Toll-like receptor 4 deficiency accelerates the development of insulin-deficient diabetes in non-obese diabetic mice. - Elke Gülden (Public Library of Science (PLoS), 2013)
Background/objective Toll-like receptors (TLR) mediate the recognition of microbial constituents and stress-induced endogenous ligands by the immune system. They may also be involved in the maintenance or break down of tolerance against autologous antigens. The aim of our investigation was to study the consequence of TLR4 deficiency on the development of insulin-deficient diabetes in the NOD mouse. Methods The TLR4 defect of the C57BL/10ScN mouse was backcrossed onto the NOD background and the effect of TLR4 deficiency on diabetes development was analysed by in vivo and in vitro studies. Results Compared to animals with wildtype TLR4 expression (TLR4(+/+)), female NOD mice carrying a homozygous TLR4 defect (TLR4(-/-)), showed significant acceleration of diabetes development, with a younger age at diabetes onset (TLR4 (+/+) 177±22 d, TLR(-/-): 118±21 d; p<0.01). Pancreata of 120 d old TLR4(-/-) NOD mice revealed increased proportions of islets with advanced stages of immune cell infiltration compared to TLR4(+/+) mice (p<0.05). TLR4 deficiency did not affect the susceptibility of islet cells to the beta cell damaging mediators nitric oxide or the inflammatory cytokines tumor necrosis factor alpha, interleukin-1 beta and interferon gamma. The lack of TLR4 further had no effect on the frequency of regulatory T-cells but reduced their capacity to inhibit T-cell proliferation. Conclusions Our findings demonstrate that TLR4 deficiency results in an acceleration of diabetes development and immune cell infiltration of islets in NOD mice. We conclude that TLR4 is involved in the progression of the insulitis process thereby controlling the development of insulin-deficient diabetes in NOD mice.